Power Distribution and Performance Analysis for Wireless Communication Networks - Zhao, Dongmei; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
N/A
Introduction -- CDMA-Based Wireless Cellular Networks -- Wireless Networks with Two-hop Relaying -- Advanced Wireless Communication Networks -- Appendix A: Irreducible Matrix and Dominant Eigenvalue -- Appendix B: Posynomial and Related Optimization Problems.
Keywords: Computer science; Computer Communication Networks; Telecommunication; Computer Science; Computer Communication Networks; Communications Engineering, Networks